Interview with Silvia Marcia Alves Siqueira: notes on the study of the representations concerning masculinity and femininity in the Ancient World - Siqueira, Silvia Marcia Alves (Romanitas - Revista de Estudos Grecolatinos, 2018)
Interview with Silvia Marcia Alves Siqueira.